The taming of the shrew - Shakespeare, William, 1564-1616. (New York : SparkNotes, 2004)
Presents the complete text to William Shakespeare's play "The Taming of the Shrew" with an easy-to-understand translation on facing pages, helping students better understand the work and its meaning.
Young Adult
Young Adult
Keywords: Man-woman relationships -- Drama; Married people -- Drama; Sex role -- Drama; Comedies; Man-woman relationship -- Drama; Married people -- Drama; Sex role -- Drama; Padua (Italy) -- Drama; Padua (Italy) -- Drama; Comedies